Banking the Black Community: An Analysis of Banking Among Baltimore's Predominately Black Communities. (3rd September 2021) - Gourrier, Al G.
Abstract : For decades, Baltimore has been negatively impacted by concentrated poverty, high levels of segregation, and crime. But the stereotypes of the city often identified as "Charm City" suffer from a distinct set of initiatives that produce "Banking Deserts" in the city's predominantly Black neighborhoods. Inadequate access to financial services leaves a community susceptive to predatory lending institutions which only create a cycle of unethical financial service practices. In addition to the lack of financial services, the absence of banking in Black communities restricts access to capital and the overall financial literacy of its residents. This research explores some of the root causes of the city's racial and social-economic divide through the lens of critical race theory (CRT), as well as analyzes where the city is today. The study looks at historical legislation that caused systematic failure and perpetuated decades of discriminatory practices and the Community Reinvestment Act (CRA) which was designed to address the access challenge in underserved communities. The decades of social inequities in Charm City, have left a social and economic divide in the city, requiring corrective action and aggressive systematic change.